Papel de sinais cromáticos na identificação de parceiros sexuais em sagüi comum (callithrix jacchus) - Oliveira, Danilo Gustavo Rodrigues de (2009)
The literature concerning color vision shows a trichromatic advantage in detecting ripe fruits and young leaves, but there are contradictory results. There is also the suggestion of this type of vision being adapted to perceive socio-sexual signals. Indeed, Old World primates utilize the skin color of conspecifics as a factor of attraction. But in New World primates there is no record of a coloration signal in the body that can be utilized by other group members. The present study aims to: 1- test whether there is a relation between coloration of body regions and ovulatory cycle in female Callithrix jacchus; 2- Determine if this species uses visual signals to choose mates that are sexually receptive. We collected feces from six females during one month to quantify progesterone concentration by EIA. Body region coloration was measured using a portable spectrometer and modeled to obtain the quantum catch of each photoreceptor, the opponency channels and chromatic distance between the points in units of JND. We recorded the behavior of six males exposed to three pairs of females with a cycling and a non-cycling female in each pair using a transparent plexiglass apparatus. The color of different body regions presented a correlation between progesterone concentration and the yellow-blue and red-green visual axes, with the genitalia as the region showing the highest correlation. The visual axis more apt to see the color variations was the yellow-blue in dichromats, and in trichromats were the red-green to face, yellow-blue to abdomen and both chromatic axes to genitalia. There was no difference in the signal detectability between trichromats and dichromats, but the perception pattern differed between the phenotypes, with a better signal detection by the dichromat phenotype 562 and the trichromat phenotype 543/562. During the behavioral experiments males presented longer gaze duration in periods of experimental manipulation and gaze duration was always longer towards cycling females compared to non-cycling females. Male locomotion during experimental manipulation was greater than in the control only during the periovulatory period of the female, indicating greater excitement. The behavior of cycling females was more active than the behavior of the non-cycling ones regarding locomotion and touching of the plexiglass division of the apparatus. Male gaze duration to cycling females increased with decreasing progesterone concentration, but none of the coloration parameters was correlated to the mate preference exhibited. This coloration signal can transmit information to animals of the group about fertility of female. Different from the intense red of the genitalia swellings of Old World primates, marmoset female genitalia became more bluish-green in the fertile period. Males chose fertile females and were able to visually identify the periovulatory period of females. Choice is related to progesterone concentration, but our results do not show relation between coloration and mate preference. Maybe some behavioral measure is associated with the choice